PENGARUH CARING DAN SPIRITUALITAS TERHADAP MOTIVASI PASIEN STROKE YANG MENJALANI FISIOTERAPI DI RUMAH SAKIT - Nunung Sitepu; Ellyta Aizar; Asrizal Asrizal; Siti Zahara Nasution (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Stroke patients often experience decreased motivation in undergoing physiotherapy, which results in a slow recovery process. Patient motivation is influenced by various factors, including the quality of care provided by nurses and the patient's level of spirituality. Caring and spirituality are believed to be able to strengthen the patient's spirit to undergo the rehabilitation process consistently. Objective: This study was conducted to examine the effect of Caring and spirituality on the motivation of stoke patients. Methods: This study used analytical research methods with a cross-sectional design. This study involved 75 respondents with stroke who underwent physiotherapy at H. Adam Malik Medan Hospital in April - August 2020 with a sampling technique, namely purposive sampling. Data collection used Caring instrument by Watson, spirituality with daily spiritual experience scale and motivation with participation motivation questionnaire with data analysis using fisher's exact test. The results showed that there was a significant relationship between caring and spirituality on motivation with each p-value of 0.001 (p-value <0.05). Conclusion: caring and spirituality each have a relationship to the motivation of stroke patients undergoing physiotherapy in the hospital